2012
DOI: 10.1002/14651858.cd003573.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Hospital at home for acute exacerbations of chronic obstructive pulmonary disease

Abstract: Table of comparisons Characteristics of included studies Characteristics of excluded studies Table 01 Percentage recruitment (number of patients entered into trial/total screened) References to studies included in this review References to studies excluded in this review Additional references

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 28 publications
6
130
0
6
Order By: Relevance
“…Figure 2 highlights the complex conditions that patients seen by the team experience and demonstrates that patients are more likely to be admitted to hospital if they have severe comorbidities or are in current receipt of LTOT ( Table 2). Similar problems were identified by Jeppesen et al (2012).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Figure 2 highlights the complex conditions that patients seen by the team experience and demonstrates that patients are more likely to be admitted to hospital if they have severe comorbidities or are in current receipt of LTOT ( Table 2). Similar problems were identified by Jeppesen et al (2012).…”
Section: Discussionsupporting
confidence: 73%
“…A systematic review of eight randomised controlled trials with 870 patients concluded that hospitalat-home schemes were safe and demonstrated a significant reduction in readmission rates and a trend towards reduced mortality rate when compared with conventional inpatient treatment of acute exacerbations of COPD (Jeppesen et al, 2012). The systematic review did, however, identify a lack of evidence of patient satisfaction in either setting and the need for future research to determine which medical professionals are most appropriate to deliver hospital-at-home services.…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews in patients with COPD have studied self-management education (11,12), integrated care (13)(14)(15), shared management between specialists and primary care physicians (16), and home care (17) in patients with stable COPD, or hospital at home for acutely ill patients with COPD exacerbations (18) or other conditions (19). Previous reviews on care transitions from hospital to home have focused on other patient populations (ie, not patients with COPD exacerbations) (20)(21)(22).…”
mentioning
confidence: 99%
“…In our trust, the COPD nurses have an instrumental role involving liaison with community respiratory teams and facilitating early supported discharge and hospital at home schemes. These reduce LoS, re-admissions, and mortality for selected patients [23,24]. Failure to ensure review of some patients by the hospital COPD nurse may have limited opportunities for post-discharge integrated care with community COPD services.…”
Section: Discussionmentioning
confidence: 99%